HUBUNGAN ANTARA KECERDASAN LOGIS-MATEMATIS DAN KEDISIPLINAN BELAJAR SISWA KELAS V SD NEGERI PAGAR AIR KABUPATEN ACEH BESAR - M Yamin; Fauzi Fauzi (Jurnal Pesona Dasar, 2021)
This study examines the existence of a logical-mathematical intelligence relationship to the learning discipline of fifth grade students at SD Negeri Pagar Air Aceh Besar District. To answer the relationship between logical-mathematical intelligence on learning discipline, researchers use a quantitative approach to the type of associative research. The sample in this study was 40 fifth grade students of Pagar Air Elementary School. Data collection techniques using tests and questionnaires. The data analysis technique used is simple regression analysis. Based on the results of data analysis shows that there is a positive and significant relationship between logical-mathematical intelligence and learning discipline of fifth grade students of SD Negeri Pagar Air. This is indicated by the value of Fcount  F table at the 5% significance level of 5.98  4.10 and the regression equation Ŷ = 76.02 + 0.99X which can predict the ups and downs of students' learning discipline. The magnitude of the influence of logical-mathematical intelligence with student learning discipline can be seen from the value of rxy = 0.370, r count is greater than rtable at a significance level of 5% ie 0.370  0.320, meaning that logical-mathematical intelligence contributes 13.69%. Thus it can be concluded that there is a significant relationship between logical-mathematical intelligence and the discipline of learning of fifth grade students at SD Negeri Pagar Air Aceh Besar.